2019
DOI: 10.1002/slct.201901142
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Macro‐Kinetics of NO Advanced Oxidation Removal by Decomposition of Gas‐Phase H2O2 over γ‐Fe2O3@Fe3O4

Abstract: Mixed maghemite–magnetite (γ‐Fe2O3@Fe3O4) has been used as catalyst for NO advanced oxidation removal under various conditions such as the reaction temperature, the feeding rate of H2O2 and the SO2 concentration in this study. The result of macro‐kinetics experiments indicate that the reaction order of NO from simulated flue gas is 1.06(CU) and 1.11(HM), respectively. The obtained first‐order activation energy for the NO removal in the presence of CU and HM were Ea=49.87KJ/mol and Ea=30.06KJ/mol, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…After absorption, it was found from peak area calculation that the content of Fe(II) decreased from 39.8% to 16.6% and the percent of Fe(III) increased from 35.4% to 52.8%. The results confirmed that a redox reaction occurred on the catalyst 49 …”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…After absorption, it was found from peak area calculation that the content of Fe(II) decreased from 39.8% to 16.6% and the percent of Fe(III) increased from 35.4% to 52.8%. The results confirmed that a redox reaction occurred on the catalyst 49 …”
Section: Resultssupporting
confidence: 72%
“…The results confirmed that a redox reaction occurred on the catalyst. 49 For O1s spectra (Fig. 9(b)), the characteristic peaks in the O1s spectrum appeared at 529.8-530.0 and 531.1-531.4 eV, corresponding to the lattice oxygen (Fe O) and adsorbed oxygen (OH , COOH ) of the catalyst, respectively.…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…Rod‐like colloids are very interesting systems and are known for their ability to form fascinating liquid‐crystal and plastic‐crystal phases . These mesophases are the colloidal analogues of molecular liquid crystals or plastic crystals.…”
Section: Figurementioning
confidence: 99%
“…[8] Thus, the Fenton-like reaction with * OH radicals from H 2 O 2 decomposition over heterogeneous catalysts would be effective and feasible for NO-oxidation. [9] Hematite, [10] hematite doped alumina, [11] zero-valent iron, [12] ferric sulfate, [7] Y-Fe 2 O 3 @Fe 3 O 4 , [13] Fe 2.5 M 0.5 O 4 [14] and Fe 2 (MoO 4 ) 3 [15] have been developed for denitrification by catalytic H 2 O 2 -producing * OH radicals, and the high NO-removal conversions were observed. However, for those catalysts, the relative low surface area might impose low utilization of active sites.…”
Section: Introductionmentioning
confidence: 99%